2016
DOI: 10.1111/jgh.13232
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone regulation of cyclin E kinase: A key factor in determining gender differences in hepatocarcinogenesis

Abstract: Testosterone is the positive regulator of hepatocyte cell cycle via cyclin E, while estradiol plays a negative role by effects of p53 and p21. Together, both sex hormones determine the male predominance of gender differences in hepatocarcinogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 32 publications
2
29
0
Order By: Relevance
“…This hypothesis has been examined in several animal studies [30, 31]. Estrogen exposure has been associated with decreased risk of HCC, while the administration of testosterone accelerated HCC development in an animal study [31]. Pok et al observed that testosterone enhanced the expression of liver cell cycle regulators, while estradiol suppressed the expression of liver cell cycle markers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This hypothesis has been examined in several animal studies [30, 31]. Estrogen exposure has been associated with decreased risk of HCC, while the administration of testosterone accelerated HCC development in an animal study [31]. Pok et al observed that testosterone enhanced the expression of liver cell cycle regulators, while estradiol suppressed the expression of liver cell cycle markers.…”
Section: Discussionmentioning
confidence: 99%
“…Pok et al observed that testosterone enhanced the expression of liver cell cycle regulators, while estradiol suppressed the expression of liver cell cycle markers. Both estrogen and testosterone hormones might jointly determine the gender discrepancy of HCC in mice [31]. On the other hand, work by Kemp et al indicated that testicular feminized mutant mice, which lack functional androgen receptors, have a similar risk of drug induced HCC compared to female mice but much less than other male mice [32].…”
Section: Discussionmentioning
confidence: 99%
“…DEN-injected female mice exhibited scarcer dysplastic foci and less acute early stage of HCC than males, with more differentiated tumors and fewer metastases [120]. Castration of these mice down-regulated cyclin E kinase and amplified hepatocyte apoptosis, and estradiol/progesterone enhanced those effects.…”
Section: Hcc Malignancy and Sex Hormonesmentioning
confidence: 94%
“…Sex differences in sex hormones appear to be important as a risk factor for HCC. Testosterone is a positive regulator of hepatocyte cell‐cycle regulators, which, in turn, accelerates hepatocarcinogenesis, in contrast estradiol, suppresses cell‐cycle regulators thereby suppressing the development of liver cancer …”
Section: Epidemiologymentioning
confidence: 99%